Flat location and size as a determinant of homeownership duration - Foryś, Iwona (Ekonomia i Prawo. Economics and Law, 2022)
Motivation: Both the research on the residential market focuses primarily on analyses of the size and quality of the housing stock, or seeking dependencies with socio-economic factors. The second research area is the analysis of prices and construction of residential price indices. As an equally important issue is assessing the intensity of trade in particular types of flat and location. A standard view is that those small flats are more frequently traded on the market than large ones. Aim: The study concerns analysis of ownership duration of a flat by the same owner (from the day of purchase to the sale day). It depends on the characteristics of the dwelling, including the location and size. The research will verify the hypothesis of a shorter duration for small units and its location. The study relies on the example of one local housing market. The study use regression analysis to examine the property value on the city’s districts and duration analysis to explore ownership duration time, and nonparametric models of a proportional model Cox gambling with explanatory variables dependent on time. Results: This research is significant in socio-spatial connection to the housing market. It shows that the current practice of buying a small flat as an investment in the housing market is appropriate. Due to the rapid price increase of small flats and high turnover, the chances for a good investment are increasing. With the help of the Cox model, the study shows that on the local market poor location in the old city housing estate and a larger floor area decreased the odds of a property to be sold quickly. The study results are valuable due to the unique role of housing on investing in the local market.